Socio-Economic-Political-Cultural Aspects in Malaria Control Programme Implementation in Southern India - S. K. Ghosh; Rajan R. Patil; S. N. Tiwari (Journal of Parasitology Research)
Objective. A Socio-economic-political-cultural (SEPC) study was undertaken under the Roll Back Malaria (RBM) initiative to understand the process of programme implementation and how far in the changing malaria context, the broader environment has been understood and programme components have undergone changes. Material and Methods. Two studies were carried out; first in four villages under the primary health unit (PHU) Banavaralu in Tiptur Taluka in September 2002 and the second one in April 2003 in four villages in Chitradurga district, namely, Kappagere, Kellodu in Hosadurga Taluka, and Vani Vilas Puram and Kathrikenhally in Hiriyur Taluka. Focus group discussion and key interviews were adopted to collect the qualitative data. Results. Gender discrimination and lack of empowerment of women came out strongly in social analysis. In the rural elected bodies called Panchayats, the concept of health committees was not known. Health committees as one of the important statutory committees under every Panchayat were nonexistent in reality in these villages. Financial difficulties at Grama Panchayat level and also meager budget allocation for health have led to indifferent attitude of Panchayat members towards health. It was observed that there were generally no specific cultural practices in relation to malaria cure. Cultural and traditional practices in malaria-related issues were not predominant in the community except for some sporadic instances. Conclusion and Recommendation. SEPC study is an important indicator in malaria control programme. It is ultimately the community that takes the major decision directly or indirectly and the health authority must guide them in right direction.